Motivasi Belajar sebagai Faktor Intrinsik Peserta Didik dalam Pencapaian Hasil Belajar - Anindita Trinura Novitasari (Departement of Mathematics Education, 2023)
Learning takes place with the role of educators and students in it who are very synergistic with each other. Educators are required to be professional in the learning process so that they can convey material messages well, through methods, strategies, approaches and techniques which of course explore the modalities of students by paying attention to the relevance of learning tools that are arranged according to the material to be conveyed. Professional educators will always do innovation and novelty in the technique of delivering material during the learning process so that learning objectives are achieved. The role of the educator as a facilitator in learning is supported by the initial potential that students already have which is directed by using the methods, approaches, learning strategies chosen by the educator will make it easy for students to absorb the material presented. Students as subjecs in the learning process should always make changes for the better. This change will be obtained through the learning process. After receiving the message in the learning process, there will be a period of receiving the message and here it needs to be supported by individual motivation which becomes an instrinsic determinant of students and has the potential to achieve learning outcomes leading to good learning achievement. Learning motivation as a form of factor that greatly influences learning outcomes becouse learning motivation strongly supports the presence of student learning independence. Students who are independent in the learning process will facilitate the absorption of messages conveyed by educators in the form of constructive learning that is currently developing. Learning motivation can be from internal factors outside of students. However, what is very influential is the intrinsic factor because it is present within each individual who is undergoing the learning process and cannot be presented by others.